WAYS TO DEVELOP ENTREPRENEURSHIP THROUGH INNOVATION - Mullabayev Baxtiyarjon Bulturbayevich; Shakirova Gulbahor Sharipdjanovna; Alabayev Sobitxon Ibragimovich (International Journal of Innovations in Engineering Research and Technology, 2021)
This article describes in detail the creation of innovative ideas and innovations to increase the efficiency of entrepreneurial activity and their application in practice. It also highlights a number of systemic issues that hinder the further improvement of conditions for the development of active entrepreneurship and innovation in our country.